2018
DOI: 10.13005/bpj/1345
|View full text |Cite
|
Sign up to set email alerts
|

Are Mangiferin and Mangiferin-Containing Plant Extracts Helpful for Iron-Loaded Transfusion-Dependent and Non-Transfusion-Dependent Thalassaemia Patients?

Abstract: Treatment of iron overload in thalassaemia is still a great burden for patients, their families and the health care system in developing countries like Indonesia, because of expensiveness and unwanted side effects of chemical iron-chelating therapeutics. This animal study investigates an extract from the leaves of Mangifera foedica L (EMF) and its major active compound, mangiferin, for chelating and antioxidant treatment of iron overload. Sixty rats were randomly divided into 10 groups: control, iron overload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Pardo-Andreau et al [12] have shown that mangiferin can form complexes with Fe (III). Such mangiferin-iron complexes can prevent the formation of free radicals and, in addition, exert scavenging activity, thereby enhancing the effectiveness of mangiferin as an antioxidant [12][13][14][15][16][17][18]. Previous studies with experimentally iron-overloaded rats had shown that oral administration of mangiferin and mangiferin-containing leaf extracts can reduce free plasma iron and to increase iron excretion via urine, if applied therapeutically, i. e., after the rats had already been successfully iron overloaded [18,19].…”
Section: Conclusion In Our Model Oral Administration Of Mangiferinmentioning
confidence: 99%
“…Pardo-Andreau et al [12] have shown that mangiferin can form complexes with Fe (III). Such mangiferin-iron complexes can prevent the formation of free radicals and, in addition, exert scavenging activity, thereby enhancing the effectiveness of mangiferin as an antioxidant [12][13][14][15][16][17][18]. Previous studies with experimentally iron-overloaded rats had shown that oral administration of mangiferin and mangiferin-containing leaf extracts can reduce free plasma iron and to increase iron excretion via urine, if applied therapeutically, i. e., after the rats had already been successfully iron overloaded [18,19].…”
Section: Conclusion In Our Model Oral Administration Of Mangiferinmentioning
confidence: 99%